2019
DOI: 10.1103/physrevmaterials.3.124204
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-enforced band crossings in trigonal materials: Accordion states and Weyl nodal lines

Abstract: Nonsymmoprhic symmetries, such as screw rotations or glide reflections, can enforce band crossings within high-symmetry lines or planes of the Brillouin zone. When these band degeneracies are close to the Fermi energy, they can give rise to a number of unusual phenomena: e.g., anomalous magnetoelectric responses, transverse Hall currents, and exotic surface states. In this paper, we present a comprehensive classification of such nonsymmorphic band crossings in trigonal materials with strong spin-orbit coupling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 82 publications
0
27
0
2
Order By: Relevance
“…However, for many materials, the spatial symmetry of the crystal structure implies that band touching can happen in the form of extended nodal structures, such as nodal lines or nodal surfaces [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Furthermore, nodal lines and nodal surfaces can also arise in parameterdependent quantum systems [22][23][24] in the presence of fine-tuning or symmetries.…”
mentioning
confidence: 99%
“…However, for many materials, the spatial symmetry of the crystal structure implies that band touching can happen in the form of extended nodal structures, such as nodal lines or nodal surfaces [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Furthermore, nodal lines and nodal surfaces can also arise in parameterdependent quantum systems [22][23][24] in the presence of fine-tuning or symmetries.…”
mentioning
confidence: 99%
“…The presented characterization of TPs applies to spinless representations in all space groups (magnetic or not, nonsymmorphic or not), and as such provides that next essential piece of information towards the growing catalogue of symmetry-protected and symmetry-enforced band nodes [52,[86][87][88]. In this regard, we conclude with one speculation that may constitute an interesting research avenue for the near future.…”
Section: Discussionmentioning
confidence: 70%
“…140) Zr 2 Ir using magnetic susceptibility, electrical resistivity, heat capacity, and muon-spin rotation/relaxation (μSR) techniques. Recent work has revealed that the nonsymmorphic symmetry can host novel topological phases [21] and topological superconductivity, thus making Zr 2 Ir an ideal candidate material. Initial band-structure calculations have revealed that Zr 2 Ir is a topological semimetal with a symmetry-enforced Fermi-level degeneracy at high-symmetry points [22,23].…”
Section: Introductionmentioning
confidence: 99%